A-site Ca/Sr co-doping to optimize room-temperature TCR of La0.7Ca0.3-xSrxMnO3 films. Issue 8 (15th April 2022) - Guan, Xiaoli; Li, Hongjiang; Gu, Xin; Yu, Zhiyuan; Jin, Shuaizhao; Yu, Xiaohan; Liu, Xiang
Abstract: Based on the analysis of crystal structure, Mn 3+ /Mn 4+ pairs, distortion of MnO6 octahedron, and electrical transport properties of La1- x Ca x MnO3 and La1- x Sr x MnO3 materials, room-temperature coefficient of resistivity ( TCR ) of La0.7 Ca0.3- x Sr x MnO3 (LCSMO) films was optimized by Ca/Sr co-doping at the A-site. LCSMO films are successfully fabricated on LaAlO3 ( 100 ) substrates via facile spin coating technology. The microstructure of LCSMO films is characterized by X-ray diffraction, Raman spectroscopy, Fourier transform infrared spectroscopy, atomic force microscopy and X-ray photoemission spectroscopy. Results reveal that A-site Ca/Sr co-doping significantly influenced crystal structure, formation of Mn 3+ /Mn 4+ pairs, and distortion of MnO6 octahedron. The correlation between microstructure and electrical transport properties was explained through the phenomenological percolation model, double-exchange mechanism and Jahn-Teller effect. Furthermore, the TCR reached 10.2% K -1 at 296.1 K in La0.7 Ca0.18 Sr0.12 MnO3 films.